Synthesis of Boron-Doped Zinc Oxide Nanosheets by Using Phyllanthus Emblica Leaf Extract: A Sustainable Environmental Applications - Khalid, Awais; Ahmad, Pervaiz; Muhammad, Saleh; Khan, Abdulhameed; Khandaker, Mayeen Uddin; Alam, Md Mottahir; Asim, Mohd; Din, Israf Ud; Iqbal, Jibran; Rehman, Ibad Ur; Razzaq, Zohaib; Pandian, Sivakumar; et al. (Frontiers in Chemistry, 2022)
The use of Phyllanthus emblica (gooseberry) leaf extract to synthesize Boron-doped zinc oxide nanosheets (B-doped ZnO-NSs) is deliberated in this article. Scanning electron microscopy (SEM) shows a network of synthesized nanosheets randomly aligned side by side in a B-doped ZnO (15 wt% B) sample. The thickness of B-doped ZnO-NSs is in the range of 20 – 80 nm. B-doped ZnO-NSs were tested against both gram-positive and gram-negative bacterial strains including Staphylococcus aureus, Pseudomonas aerugino-sa, Klebsiella pneumonia, and Escherichia coli. Against gram-negative bacterium (K. pneumonia and E. coli), B-doped ZnO displays enhanced antibacterial activity with 26 mm and 24 mm of inhibition zone respective-ly. The mass attenuation coefficient (MAC), linear attenuation coefficient (LAC), mean free path (MFP), half-value layer (HVL), and tenth value layer (TVL) of B-doped ZnO were investigated as aspects linked to radiation shielding. These observations were carried out by using a PTW® electron detector and VARIAN® irradiation with 6 MeV electrons. The results of these experiments can be used to learn more about the radiation shielding properties of B-doped ZnO nanostructures.